Correlation Dental Classification of Mandibular Impacted Tooth with a Duration of Action Odontectomy in Rumkital Dr. Ramelan Surabaya - Muhammad Rizki Zulian; Eddy Hermanto; Sudibyo (Denta Journal Kedokteran Gigi, 2017)
Background: Odontectomy actions require a relatively longer time compared tothe usual tooth extraction because there are basic steps or stages in a procedural plan of action as well as the difficulty of the position of the teeth. Purpose: Knowing the relationship of classification third molar teeth impaction with long of odontectomy treatment in Rumkital Dr. Ramelan Surabaya. Materials and Methods: The type of this research is observational with cross sectional approach. Sampling was done by total sampling in patients of third molar teeth impaction under the treatment odontectomy in Rumkital Dr. Ramelan Surabaya during March and April 2015. The data was collected prospectively by recording the length of time the action starts odontectomy suturing of the incision using the stopwatch and panoramic radiography result and medical consent form action. Result:.Class I based positioning and angulation showed that the fastest is the class IA mesioangular with 3 patients with an average time of 12 minutes 14 seconds and the longest is the vertical IA class by 4 people with an average time of 15 minutes 42 seconds. Class IIA is vertical with 12 patients with an average time of 12 minutes 57 seconds and the longest is the class IIB in 1 patient distoangular average time of 38 minutes 56 seconds. Class IIIC mesioangular with 3 people on average time of 19 minutes 42 seconds and the longest is the horizontal IIIC class II patients with an average time of 44 minutes. Conclusion: Classification of impacted third molar teeth under the Class I has the fastest time (13 minutes 56 seconds) when compared to Class II (18 minutes 14 seconds) and class III (29 minutes 12 seconds), while based on the depth position C has the most time long with horizontal angulation.